PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA PADA MATA PELAJARAN IPS TERPADU - Dessy Triana Relita; Santo Petrus; Yulia Suriyanti (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
Learning media can help teachers by offering explanations for the lessons that need to be taught. The purpose of this project is to create instructional materials for Snakes and Ladders in social studies for class VIII at SMP Panca Setya 2 Sintang in the academic year 2022–2023. Research and development research utilizing the ADDIE model is the research methodology used. Studying through experiments design for a single subject experiment. Both qualitative and quantitative data are present in the research data. For the school year 2022–2023, 25 eighth-grade SMP Panca Setya 2 Sintang students served as the research subjects. using surveys, observation, and documentation as data collecting methods. Product practicality and feasibility assessments are part of data analysis. The findings of this study are presented in the form of educational media materials for the social studies game of snakes and ladders for class VIII junior high school pupils. Based on the media's classification as very good, the feasibility evaluation was made. The material's viability is rated as being very good. Evaluation of usefulness using very doable standards. According to the questionnaire, the SMP Panca Setya 2 Sintang IPS students' and teachers' responses in terms of materials and media are rated as meeting very good requirements